ECO-INNOVATIVE SOLUTIONS IN FOOD PACKAGING: IMPACT ON SUSTAINABLE DEVELOPMENT AND CONSUMER PREFERENCES - Тягунова, Наталія (SWorldJournal, 2026)
The article examines eco-innovative solutions in food packaging as a key driver of sustainable development and a determinant of consumer preferences in modern markets. Growing regulatory pressure, the transition toward a circular economy, and increasing